KONSEP PENDIDIKAN HOLISTIK DALAM MEMBINA KARAKTER ISLAMI - Fitria Wulandari; Tatang Hidayat; Muqowim (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
Education that is built on modern view (Cartesian-Newtonian) is considered to have given birth to various problems for the development of the nation's children, especially out put education that has an instrumentalistic personality, materialistic, boxed, dichotomic, very weak in terms of the character and personality of the nation and religion. This research aims to describe the concept of holistic education in fostering Islamic character that is able to answer the problem of out put education today. This research uses qualitative approach and literature study method. In its implementation, the collected data is analyzed using descriptive analysis methods. Based on the results of the discussion, the concept of holistic education sees education as a conscious effort to develop its own potential as a unique and holistic human being as God's perfect creation. Through holistic education, learners are helped in developing their potential in a more enjoyable learning atmosphere (learning is fun) and put forward deliberation through experience in interacting with their environment, learners can be themselves (learning to be), not limiting to three domains only but demanding to pay attention to all the needs and potentials they have to foster the Islamic character of learners.